Legal Analysis Of Successor Heirs In Positive Law And Islamic Law - Jamillah, Jamillah (International Asia Of Law and Money Laundering, 2023)
This study is intended to find out more in the provisions in the compilation of Islamic law and Civil Law, on the status successor heirs. Because there is a slight difference, if in BW replacement is no limit, then in KHI explained that this replacement only comes to grandchildren course, therefore there is a contradiction between the provisions of the expert successor inheritance in the compilation of Islamic law with Civil Law (BW). The study was conducted qualitatively using the juridical-normative approach. Approach normative done by researching library materials includes research on the principles of law, Systematics law, comparative law and legal history. The Data obtained by the documentation technique is then performed inductive analysis, where after the data collected then the next step is to analyze the data that is a way to search and systematically organize records of results interviews, observations and more. The results of this study can be explained that the law of inheritance according to the compilation of slam law stated that grandchildren have the right to replace the position his parents died before heir, although the share of grandchildren is not always as big his parents. The share of grandchildren should not exceed the share other heirs equal to the one he replaced. As for provisions in the law of inheritance according to civil law that not only grandchildren have the right to take the place of people the old man who died but also a nephew and also siblings can be replaced by his children.